ANALISIS RISIKO HARGA KOMODITAS SAYURAN UNGGULAN DI INDONESIA - Astuti Rahmawati; Anna Fariyanti (Forum Agribisnis, 2018)
Chilies, potatoes, shallots, and cabbage are five main vegetables that have high rates of production, but they also have high levels of price fluctuation. The purpose of this study was to analyze the levels of price risk and analyze alternative strategies needed to reduce the price risk of chilies, potatoes, shallots, and cabbage. The method of analysis that used in this research is ARCH/GARCH model, Value at Risk (VaR), and coefficient variation. The results showed that the price of chilies, tomatoes, and potatoes were influenced by price volatility and variants in previous periods. The price volatility and variants of shallots and cabbages were influenced by the prices of one and two previous periods. The calculation of VaR, which was based on the total capital in a one-day sale period showed that price risk of chilies, potatoes, shallots, and cabbage were at 4.077 persen, 3.078 persen, 5.240 persen, 6.879 persen, dan 3.980 persen. Based on coefficient variation showed that tomatoes had the highest price risk was at 0.428 while potatoes was found to have the lowest price risk was at 0.080. Shallot had the second highest price risk was at 0.195. Cabbage and chilies had the third and the forth highest price risk were  at 0.209 and 0.349. Alternative strategy to solve the price risk of vegetables need to be applied by traders, farmers, and government.